Harta dalam Islam Sebagai Landasan Penyajian Laporan Posisi Keuangan Syariah : Tinjauan Konseptual dan Aplikatif - Rezki; Muh.Rifky Bahar; Masyhuri (Journal of Islamic Economic Studies, 2025)
This study aims to examine the concept of wealth in Islam as the foundation for presenting the Islamic financial position report both conceptually and applicatively. The method used is a literature study with a qualitative descriptive approach, reviewing literature related to the principles of ownership and management of wealth according to Sharia as well as Islamic accounting standards, particularly PSAK 101. The findings indicate that wealth in Islam is regarded as a trust that must be managed based on the principles of permissibility (halal), justice, and social responsibility, so that the Islamic financial position report must reflect transparency, accountability, and compliance with Sharia values. The presentation of the report is not only oriented toward financial aspects but also supports the maqashid shariah in maintaining the welfare of the community. However, challenges such as practitioners’ understanding and public literacy still need to be addressed through education and regulatory strengthening to ensure that Islamic financial reports can function optimally as fair and sustainable financial instruments.